Оцінювання значення, життєздатності та перспектив розвивання атомної енергетики у реалізуванні післявоєнної енергетичної стратегії України: соціально-економічний аспект - Завербний, А.С.; Осадча, Н.В. (Вісник економічної науки України, 2024)
У статті досліджено сучасні проблеми системи управління відходами, обґрунтовано і систематизовано теоретичні і практичні підходи щодо впровадження цифрових технологій і штучного інтелекту у систему управління відходами, перспективи використання технологій штучного інтелекту у вирішенні завдань оперативного і стратегічного управління. Розкрито переваги інтеграції цифрових технологій і штучного інтелекту у системі управління відходами для організації збору, утилізації, транспортування, переробки, знешкодження відходів, моніторингу та регулювання процесів на всіх етапах. Ідентифіковано та наведено труднощі і проблеми на шляху широкого застосування штучного інтелекту у системі управління відходами. Визначено роль впливу дисбалансу між професійними навичками працівників і вимогами роботодавців у процесах автоматизації виробництва та необхідністю переходів до моделей Індустрії 4.0 та Індустрії 5.0. Дослідження включає результати із таких ключових аспектів: цілісне осмислення нових викликів та перспектив впровадження цифрових технологій і штучного інтелекту у системи управління відходами; появи ризиків цифрової кризи; застосування штучного інтелекту на рівні логістики; взаємодії з клієнтами та постачальниками; передбачення обсягів відвантажених відходів; досвіду та успішності системи управління відходами закордонних компаній; індексу цифрової інтенсивності використання цифрових технологій; формування кібер-ризиків та наслідків цифровізації; економіки чистого нуля; процесів ефективності формування звітності та співпраці з державною службою статистики; сфери штучного інтелекту у людських мотивах прийняття рішень; втраченої фінансової вартості на звалищах і при спалюванні. Стаття завершується висновками, які підкреслюють значення власного бачення сучасної парадигми системи управління відходами у забезпеченні розвитку економіки у контексті цифровізації економіки та особливостей використання штучного інтелекту. The article highlights the theoretical and applied foundations of research and assessment of the significance, viability, role, and prospects of nuclear energy development in the implementation of the post-war energy strategy of Ukraine. The socio-economic aspect of this issue is analyzed. The energy sector plays an extremely important role for any country today. The country’s energy sector is strategic and belongs to the critical infrastructure. The industry provides energy resources for the efficient functioning of industry, transport, agriculture, social sector, etc. through its uninterrupted operation. The energy sector, acting as an integral part of the infrastructure, directly affects the level of competitiveness of each country’s economy. Therefore, it is important to study the conditions for systematic, uninterrupted supply of energy resources (including energy resources for nuclear power) to the country’s economy. Nuclear power is a significant component of Ukraine’s energy sector. The following research methods were used in the study: morphological method, sieve analysis, scenario method, analog method. The importance of nuclear energy is emphasized. The article analyzes the global generation. The paper analyzes the structure of energy production in the world as of 2023. Nuclear energy production in the world by continents is analyzed. The study presents the geographical structure of the world’s uranium needs and the structure of its global production. The forecasted parameters of the dynamism of production and the exhaustion of traditional energy resources are calculated. In developing the national and global nuclear power industry, the primary task is to ensure the required level of safety in the use of nuclear energy and to develop measures to extend the lifetime of nuclear power units. The construction of new high-capacity domestic nuclear power plants will be limited for decades by financial possibilities due to uncertainty of future economic development. It is optimistic to predict the participation of investment capital in the development of domestic small nuclear power. Given the current state of the Ukrainian energy sector, the special significance of nuclear energy in providing electricity to consumers in the war and postwar periods is clearly understood. Implementation of advanced nuclear power technologies in Ukraine will allow the country to ensure energy independence, and thus political and economic independence, in the postwar period.